2020
DOI: 10.1080/20013078.2020.1778883
|View full text |Cite
|
Sign up to set email alerts
|

miR‐23a‐3p‐abundant small extracellular vesicles released from Gelma/nanoclay hydrogel for cartilage regeneration

Abstract: Articular cartilage has limited self-regenerative capacity and the therapeutic methods for cartilage defects are still dissatisfactory in clinic. Recent studies showed that exosomes derived from mesenchymal stem cells promoted chondrogenesis by delivering bioactive substances to the recipient cells, indicating exosomes might be a novel method for repairing cartilage defect. Herein, we investigated the role and mechanism of human umbilical cord mesenchymal stem cells derived small extracellular vesicles (hUC-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
211
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(217 citation statements)
references
References 55 publications
6
211
0
Order By: Relevance
“…Liu X confirmed that the imine cross-linked hydrogel containing MSC-Exos has the ability to promote cartilage regeneration [ 55 ], but the mechanism and role of MSC-Exos in the process of cartilage regeneration are still unclear. Our study confirms that hWJMSC-Exos can promote the migration and proliferation of BMSCs in vitro and can promote the proliferation of chondrocytes, which is consistent with the results of Hu H's research [ 62 ]. Studies by Zhang S [ 63 ] and Woo CH [ 47 ] confirmed that Exos derived from human embryonic stem cell-derived MSCs and human adipose-derived MSCs have similar biological functions.…”
Section: Discussionsupporting
confidence: 91%
“…Liu X confirmed that the imine cross-linked hydrogel containing MSC-Exos has the ability to promote cartilage regeneration [ 55 ], but the mechanism and role of MSC-Exos in the process of cartilage regeneration are still unclear. Our study confirms that hWJMSC-Exos can promote the migration and proliferation of BMSCs in vitro and can promote the proliferation of chondrocytes, which is consistent with the results of Hu H's research [ 62 ]. Studies by Zhang S [ 63 ] and Woo CH [ 47 ] confirmed that Exos derived from human embryonic stem cell-derived MSCs and human adipose-derived MSCs have similar biological functions.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Aubin et al attempted to change the proliferative arrangement of different cells using micropatterned GelMA to provide a theoretical basis for constructing functional tissues in vitro [43]. Zou et al used GelMA to construct biomimetic bone with a trabecular bone structure and Hu et al used GelMA microspheres loaded with small extracellular vesicles to promote cartilage regeneration [44,45]. In the current study, GelMA was used as a carrier of ADSC-Exos to provide a good microenvironment for exosome storage and their gradual absorption.…”
Section: Discussionmentioning
confidence: 99%
“…As EVs maybe cleared rapidly from joint space, they have been used as therapeutic substances encapsulated and embedded in drug-delivery systems consisting of different matrices, which help to achieve sustained effects. These biomaterials are photo-induced imine crosslinking hydrogel glue, gelatin methacrylate/nanoclay hydrogel or solid 3D printed cartilage ECM/gelatine methacrylate (GelMA) scaffolds (Liu et al, 2017b ; Chen et al, 2019 ; Hu et al, 2020 ). Liu et al implanted an acellular tissue patch (EHG) consisting of a hydrogel glue blended with human iPSC-MSC-EVs into a rabbit articular cartilage defect.…”
Section: Therapeutic Application Of Msc-evs In Musculoskeletal Disordmentioning
confidence: 99%